Why Non-Clinicians Should Not Be Doing Clinical Ethics - Rohin Bhatt (Voices in Bioethics, 2022)
Photo by National Cancer Institute on Unsplash “An expert is someone who knows some of the worst mistakes that can be made in his subject, and how to avoid them.” ― Werner Heisenberg INTRODUCTION Bioethicists have long debated the question of expertise in clinical ethics and who gets a say in bedside clinical ethics consults.[1] From Seattle’s famous God Committee that decided on the allocation of kidneys, to clinical ethicists at a suburban hospital in Ohio, clinical ethics ‘experts’ have been central to bioethics and its development.[2] However, it is time to question what expertise in clinical ethics means, and if there can ever be such an expert. Does expertise mean proficiency in clinical care or the ethics part of clinical ethics? Should professionals who are not healthcare practitioners be involved in clinical ethics discussions? In this paper, I argue that clinical ethics consults involving non-clinicians should be done away with for two reasons: first, they lack clinical medical experience to properly analyze the ethical issues, and second, moral expertise should give way to medical expertise. Although clinical ethics consultants might venture into areas of clinical expertise with a bona fide intention of helping patients or surrogates, their judgment is often based on knowledge of ethical theories.[3] However, bioethicists have cautioned against a casuistic method and signaled for clinical ethicists to have clinical experience and medical education.[4] While it is perfectly possible to familiarize oneself with the law and ethics, I argue that it is not possible to appreciate the complexity of certain medical decisions entirely without medical experience.[5] Bedside ethical conundrums are unique and impact every patient differently. Thus, when an ethics consultant or a healthcare practitioner draws on a single bedside dilemma and applies the knowledge gained from it to a different patient or a different dilemma, they may find themselves creating bad rules and ignoring autonomy. As non-clinicians who sit on ethics committees have no bedside clinical experience, their magnitude of transformative experiences (experiences that give the subject knowledge that would otherwise be otherwise unavailable)[6] is limited. The clinicians develop such experiences over time giving care. The ethics committee members do not have a similar way to gain experience. This also speaks to the importance of a phenomenological reading of clinical ethics decisions. Specifically, clinical ethics consultants without sufficient medical expertise may fail to guide patients in the best way possible in making medical decisions. A confined and parochial, or purely philosophical, approach that non-clinicians often use might not be in the best interests of the particular patient. If they were to venture into clinical situations to comment on the ethical aspect, they could step into matters they know little about which might end up causing harm to the patient. We, as bioethicists, would be doing a disservice to patients if we let non-clinicians claim the moral high ground in the face of medical advice. As Scofield puts it, “(Clinical) Ethics consultation is and can only be what it purports not to be—a moral, if not an ethics, disaster. It has acted unprofessionally because … of its failure to do what a profession worthy of the name would do.”[7] l. Medical Expertise May Be More Appropriate than Moral Expertise An idea that a clinical ethics consult should be conducted by clinicians themselves comports with the makeup of clinical ethics committees. They are usually comprised primarily of medical professionals, but increasingly hospitals are attracting more ethics professionals who are not healthcare practitioners. As Hauschildt and De Vires note, “a closer examination suggests that clinical ethicists are likely to be clinicians themselves and that clinical considerations are often the ultimate authority in defining what is, and is not, determined to be ethical.”[8] In cases that are reported to ethics consults, 63 percent show a disagreement between the patient and the doctor about the course of treatments.[9] Those disagreements speak to ethical issues. For example, if a doctor recommends palliative care and patient wants to pursue an aggressive course of treatment, the ethical dilemma is built into the clinical care decision. While we would like to think that ethicists on hospital ethics committees deliberate on philosophical nuances of treatment (or the lack thereof), I argue that clinical ethics consults focus on resolving clinical ambiguities and reaching consensus, which ultimately relies on clinical judgment. An ethics consultant may not be able to appreciate the medical nuances of the situation. Studies conducted have clearly demonstrated that most ethics consults are called in when there is a lack of communication.[10] What would serve the patients, in this case, is perhaps investing the money that is spent in training and employing non-clinician consultants into teaching doctors and nurses how to communicate better. ll. Authoritarian Ethics Consults As with healthcare workers delving into ethics advice, in clinical ethics consults, there is a risk that the consultant might adopt an “authoritarian approach”[11] and impose his or her values, priorities, and/or religious convictions on the patients and their families. It is inevitable that in the work of bioethics, the personal meets the professional. Even if they do not mean to impose their values on the patients, there is strong empirical data to suggest that in most clinical ethics consults, patients end up following recommendations of the ethics committees. For example, in a study conducted of 229 clinical ethics consults, approximately 88 percent of the recommendations were followed. Certain types of consults such as initiating a palliative care treatment or proceeding with life-sustaining intervention had a 100 percent compliance rate with the ethics committee’s advice.[12] Additionally, studies have shown that clinicians frame consults in a way that nudges the patients in making decisions that maximize their welfare and is seen as an acceptable form of paternalism.[13] Yet, patients likely do not appreciate paternalistic nudges. In the studies, most questions were about futility or the withdrawal of life-sustaining treatment. Arguably, these questions require clinical expertise and not ethical expertise. A clinician or a nurse may be better suited to help guide the patient’s family because they would be able to comprehend and explain the complexity of the clinical case to the family better. If the idea of a clinical ethics consult is to further patient autonomy, it is failing. lll. Addressing Counterarguments Two arguments may challenge a proposal as radical as kicking all the ethics consultants who are not also medical professionals or healthcare practitioners out of clinical ethics consults or committees: first, the argument that a broader variety of professionals should have a say in bioethics; and second, that ethics committee members may relate to patients more effectively than some physicians and other healthcare workers do. Yet, these claims are not strong rebuttals. As bioethics developed within philosophy, it may have lost sight of the day-to-day ethical issues that arise in the clinic. Komesaroff argues that the task of handling clinical ethics consults is only one that clinicians can handle, and there is a need to separate bioethics from clinical ethics. He suggests that the time is ripe for clinical ethics to be considered through the lens of micro-ethics and established as an area of research distinct from bioethics.[14] I agree and assert that there is a need to distinguish the broader ethical debate from the work of everyday clinical practice, a work where clinicians are best suited to handle the issues, perhaps a subcategory of bioethics. This will involve the need for redefining the relationship between the macro ethical work of bioethics, and the micro ethical work of everyday medical/clinical ethics which happens at the bedside.[15] What is required in a clinical ethics setting, in my opinion, is for the doctor not to frame the issue in terms of bioethical or large philosophical concepts such as autonomy or deontology, but to talk to the patient and more importantly, listen to the patient. A smooth communication structure, if put in place, would help alleviate fear and establish a common ground on which decisions can be reached in clinical settings. That is, I see clinical ethics as also not necessary to the doctor-patient relationship but argue that better communication would help patients make important decisions. The ethics ultimately would belong to the patient, with the clinician providing necessary data that will help guide patient decision making and do no more. The second issue is relatability. Clinicians are often constrained by their vocabulary and medical expertise and may not be able to break down the complex pathology of a disease to the patients. Thus, some may argue that non-clinicians, not held back by the jargon, would be able to relate to the patient. As I proposed earlier, the money spent hiring and training clinical ethics consultants could be redirected to teaching doctors how to be more effective communicators. That would perhaps further patient autonomy. Nurses may also make effective interlocutors between patients and doctors in cases where the doctor cannot get through to the patient. Nurses are often involved more in the day-to-day dealing with the patient and thus know the patient and their families closely. Secondly, they possess the requisite medical knowledge to help the patients through decision-making processes. Yet the current shortage of nurses also poses issues in this realm. Some doctors and nurses make a point to get to know the patients, their beliefs, and their goals of care and could thus be better at helping patients arrive at decisions by using open jargon-free communication. CONCLUSION Much of this paper stems from my experiences as a Master of Bioethics candidate at Harvard Medical School. As a non-clinician who studied clinical ethics for a semester, under excellent guidance, I often found myself turning to friends who had clinical experience with questions about the medical aspects of case discussions. More often than not, the clinical insight that they gave me helped me better understand the choices that were before me as a purported expert in simulations. I have been plagued with the question-- would I be qualified to consult in clinical ethics, after a Master of Bioethics degree at Harvard Medical School? My answer would be an unequivocal NO. While I expect to be highly qualified to weigh in at the policy level and I have been provided the skillset necessary for in-depth philosophical analysis of complex bioethical issues, I have not become, and I suggest others are not as well, a moral expert (if there is such a thing). The hubris of a bioethicist should not get in the way of patient care. I do not mean to say through this paper, that non-clinicians are to be brushed aside is bioethical discussions. Lawyers, ethicists, chaplains, and the diverse set of people that are attracted to the work of bioethics provide an incredibly diverse set of skills, knowledge, and views that the clinicians often miss. They discuss and bring in perspectives from a variety of vantage points which have been instrumental in furthering the debates in bioethics. But as I have argued, they need not populate clinical ethics committees where they are at risk of exerting moral expertise, especially as their ethics position on a case may not be grounded in a deep enough understanding of the medical issues at hand. Instead, they should be used in broad policy-making decisions, framing issues, debating in print and digital media, and on IRBs. Bioethics is “everyone’s business,”[16] but clinical ethics should not be. - [1] Jan Crosthwaite, ‘In Defence of Ethicists. A Commentary on Christopher Cowley’s Paper’ (2005) 8 Medicine, Health Care and Philosophy 281 accessed 11 December 2021, Jukka Varelius, ‘Is Ethical Expertise Possible?’ (2008) 11 Medicine, Health Care and Philosophy 127 accessed 11 December 2021, Christopher Cowley, “A New Rejection of Moral Expertise,” Medicine, Health Care and Philosophy 8, no. 3 (November 2005): 273–79, https://doi.org/10.1007/s11019-005-1588-x.Ana S. Iltis and Lisa M. Rasmussen, “The ‘Ethics’ Expertise in Clinical Ethics Consultation,” Journal of Medicine and Philosophy 41, no. 4 (August 2016): 363–68, https://doi.org/10.1093/jmp/jhw013. [2] Albert R. Jonsen, “The God Squad and the Origins of Transplantation Ethics and Policy,” Journal of Law, Medicine & Ethics 35, no. 2 (2007): 238–40, https://doi.org/10.1111/j.1748-720X.2007.00131.x. [3] Albert R. Jonsen, “Casuistry as Methodology in Clinical Ethics,” Theoretical Medicine 12, no. 4 (December 1991): 295–307, https://doi.org/10.1007/BF00489890. [4] Matthew A. Butkus, “The Necessity of Clinical Experience in Medical Ethics Expertise,” in Moral Expertise: New Essays from Theoretical and Clinical Bioethics, ed. Jamie Carlin Watson and Laura K. Guidry-Grimes (Cham: Springer International Publishing, 2018), 227–44, https://doi.org/10.1007/978-3-319-92759-6_13. [5] Butkus. [6] L. A. Paul, “What You Can’t Expect When You’re Expecting,” Res Philosophica 92, no. 2 (2015): 149–70, https://doi.org/10.11612/resphil.2015.92.2.1. [7] Giles R. Scofield, “What Is Medical Ethics Consultation?” Journal of Law, Medicine & Ethics 36, no. 1 (2008): 95–118, https://doi.org/10.1111/j.1748-720X.2008.00241.x. [8] Katrina Hauschildt and Raymond De Vries, “Reinforcing Medical Authority: Clinical Ethics Consultation and the Resolution of Conflicts in Treatment Decisions,” Sociology of Health & Illness 42, no. 2 (February 2020): 307–26, https://doi.org/10.1111/1467-9566.13003. [9] Katrina Hauschildt and Raymond De Vries, ‘Reinforcing Medical Authority: Clinical Ethics Consultation and the Resolution of Conflicts in Treatment Decisions’ (2020) 42 Sociology of Health & Illness 307 accessed 12 December 2021, G DuVal, ‘What Triggers Requests for Ethics Consultations?’ (2001) 27 Journal of Medical Ethics 24 accessed 12 December 2021. [10] Raymond De Vries, “Regarding Bioethics: A Sociology of Morality,” Perspectives in Biology and Medicine 60, no. 1 (2017): 74–92, https://doi.org/10.1353/pbm.2017.0020. [11] H. Tristram Engelhardt, “Core Competencies for Health Care Ethics Consultants: In Search of Professional Status in a Post-Modern World,” HEC Forum: An Interdisciplinary Journal on Hospitals’ Ethical and Legal Issues 23, no. 3 (September 2011): 129–45, https://doi.org/10.1007/s10730-011-9167-4. [12] Jessica Richmond Moeller et al., “Functions and Outcomes of a Clinical Medical Ethics Committee: A Review of 100 Consults,” HEC Forum 24, no. 2 (June 2012): 99–114, https://doi.org/10.1007/s10730-011-9170-9. [13] Ajay Aggarwal, Joanna Davies, and Richard Sullivan, “‘Nudge’ in the Clinical Consultation – an Acceptable Form of Medical Paternalism?,” BMC Medical Ethics 15, no. 1 (December 2014): 31, https://doi.org/10.1186/1472-6939-15-31. [14] Paul A. Komesaroff, “From Bioethics to Microethics: Ethical Debate and Clinical Medicine,” in Troubled Bodies, ed. Paul A. Komesaroff (Duke University Press, 1995), 62–86, https://doi.org/10.1215/9780822379782-004. [15] Robert Sokolowski, Moral Action: A Phenomenological Study (Bloomington: The Catholic University of America Press, 2017). [16] Amy Gutmann, Everybody Wants to Go to Heaven but Nobody Wants to Die: Bioethics and the Transformation of Health Care in America, First Edition (New York: Liveright Publishing Corporation, 2019).